PERSEPSI PELANGGAN TERHADAP PELAYANAN PT. PLN (PERSERO) RAYON RANAM - Siti Khodijah; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Perception is an internal process that allows us to choose , organize and interpret stimuli from our environment and the processes that affect us . Electricity is one of the very basic need to support human life . The existence and empowerment of electric energy is a must as the driving force of the life of a nation to keep moving and pointing forward . Without the presence and empowerment of electrical energy , it will hinder to stop the activities of the business community and the home, as well as the endless delays and interruptions in the progress of a nation . Electricity is one of the factors that are essential to people's lives without electricity , the construction will not run as expected . The need for electricity for every strata of society ( household ) and government institutions as well as for the business world to show an increase every year.Perception is an internal process that allows us to choose , organize and interpret stimuli from our environment and the processes that affect us . Electricity is one of the very basic need to support human life . Research using qualitative descriptive methods based on primary and secondary data sources and data collection techniques using observation , interviews and documentation , with the determination of the informants through purposive sampling is a technique in which researchers deliberately chose certain people based on objective and research needs . Data were analyzed using analysis model of Miles and Huberman interactive data by collecting data obtained are then processed to be reduced , served to produce a general conclusion.Perception is an internal process that allows us to choose , organize and interpret stimuli from our environment and the processes that affect us . Electricity is one of the very basic need to support human life . The results showed that customers' perception of service PT . PLN ( Persero ) Rayon Panam unsatisfactory . Customers expect that service PT . PLN ( Persero ) Rayon Panam further enhanced so that customers feel comfortable and satisfied . Should the PT . PLN ( Persero ) give a good service and maximum to its customers. There are some things that need to be repaired assessed so that customers can enjoy more leverage and obtain information in accordance with the requirements, such as a welcoming and friendly service .Keywords: Perception Of Customer Service, PT.PLN (Persero) Rayon Panam unsatisfactory